PENGENALAN DAKWAH DIGITAL MELALUI SIARAN PODCAST PROGRAM NGAJI YUK DI CHANEL YOUTUBE KAUM PODCAST KEPADA MAJELIS TAKLIM BAITURRAHMAN PESONA BANYU ASRI - Endang Rahmawati; Nurliya Ni’matul Rohmah (Universitas Muhammadiyah Mataram, 2024)
The current industrial revolution era has changed the entirety of human life both in terms of socializing, working and thinking. Advances in communication technology have crippled territorial boundaries and human physical contact which was replaced by digital coded links. Da'wah activities are no longer carried out in mosques that require mad'you to come to the assembly to gain religious knowledge. Because da'wah has been rife through digital media, which has become known as digital da'wah. This service aims to introduce the public that digital da'wah also provides many benefits for people who live with advances in increasingly sophisticated communication technology. This activity is carried out by socializing as well as inviting partners to participate directly to increase partners' knowledge and experience about digital da'wah. Da'wah activities have now been carried out with various versions and methods that are more in line with the current times, one of the digital da'wah media that is currently trending is podcast broadcasts. The introduction of digital da'wah through podcast broadcasts has many benefits and relevance in the context of today's modern society which is increasingly connected through digital technology.Keywords: Digital Da'wah; Podcast Broadcasts; Chanel Youtube